Gastrointestinal Symptoms of Monkeypox Infection: A systematic review and meta‐analysis. Issue 4 (6th April 2023) - Simadibrata, Daniel Martin; Lesmana, Elvira; Pratama, Muhammad Iqbal Adi; Annisa, Nagita Gianty; Thenedi, Kevin; Simadibrata, Marcellus
Abstract: Since early May 2022, outbreaks of Monkeypox (Mpox) cases have emerged and become a global concern. Studies exploring the gastrointestinal symptoms and/or liver injury of Mpox are still very limited. This systematic review and meta‐analysis is the first to summarize the gastrointestinal symptoms reported by Mpox patients. We searched for Mpox studies published until October 21, 2022, in MEDLINE, EMBASE, SCOPUS, and organization websites. Mpox studies were observational studies that reported at least one of either gastrointestinal symptoms and/or liver injury in Mpox patients. Meta‐analysis was done to obtain the pooled prevalence of gastrointestinal symptoms in Mpox patients. Subgroup analyses were done based on the study location, age groups, and Mpox Clades. The quality of included studies was assessed using the NIH Quality Assessment Tool. Overall, 31 studies that reported gastrointestinal symptoms and/or liver injury in Mpox patients were included. The reported gastrointestinal symptoms were abdominal pain, anorexia, diarrhea, nausea, and vomiting. There is a lack of reporting for liver injury. The most prevalent gastrointestinal symptoms in Mpox patients were anorexia (47%; 95% confidence interval [CI] 41%–53%), followed by vomiting (12%; 95% CI 11%–13%), nausea (10%; 95% CI 9%–11%), abdominal pain (9%; 95% CI 8%–10%), and diarrhea (5%; 95% CI 4%–6%). Additionally, the prevalence of proctitis, rectal/anal pain, and rectal bleeding were 11% (95% CI 11%–12%), 25% (95% CI 24%–27%), and 12% (95% CI 11%–13%), respectively. Anorexia was the most frequently reported gastrointestinal symptom in Mpox patients, followed by vomiting, nausea, abdominal pain, and diarrhea. Proctitis is a novel presentation of Mpox in the 2022 outbreak.